GE_GERICHTE A/353/2025 vom 31. März 2025 - GE Cour de justice (2025)
RETARD;RESTITUTION DU DÉLAI;DÉLAI LÉGAL;NOTIFICATION IRRÉGULIÈRE;FÉRIES JUDICIAIRES | LIFD.140.al1; LIPP.49.al1; LPA.63.al2.lete; LPA.47